Peran Koperasi Pesantren (Kopontren) dalam Meningkatkan Perekonomian Pondok Pesantren Al-Jauharen Kelurahan Tanjung Johor Kecamatan Pelayangan - Putri Indah Susila Wati; Rafidah Rafidah (ARZUSIN, 2025)
The Koperasi Pondok Pesantren (Kopontren) is a form of community-based economic institution with significant potential to foster self-reliance and prosperity within Islamic boarding schools (pesantren). However, in several locations, the strategic role of Kopontren has not been fully realized. This study aims to explore in depth the role of Kopontren in improving the economic condition of Pondok Pesantren Al-Jauharen in Tanjung Johor Subdistrict, Pelayangan District. A descriptive qualitative approach was employed, with data collected through non-participatory observation, structured interviews with 16 key informants, and documentation. Data validity was ensured through source and method triangulation, while data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The findings indicate that the contribution of Kopontren to the pesantren’s economy remains limited due to constraints in capital, weak managerial capacity, and low member participation. Furthermore, the Kopontren has not yet been able to implement strategic programs that significantly impact infrastructure development and teacher welfare. These findings suggest that the success of a cooperative is not solely determined by its institutional presence but also by the strength of its governance, financial support, and member trust. The study concludes that institutional strengthening strategies are needed through economic empowerment approaches and the application of modern cooperative management to sustainably optimize the role of Kopontren in enhancing pesantren welfare.